2020
DOI: 10.1080/15427528.2020.1771643
|View full text |Cite
|
Sign up to set email alerts
|

A novel intragenic marker targeting the ectodomain of bacterial blight-resistance gene Xa21 for marker-assisted selection in rice

Abstract: BackgroundAmong the diseases in rice (Oryza sativa L.), bacterial leaf blight (BLB) caused by Xanthomonas oryzae pv. oryzae results in devastating economic losses, both in terms of yield and quality. The Xa21 mapped to the rice chromosome 11, is known to convey resistance against BLB by its involvement in plant pathogen recognition and immunity responses. The closely-linked sequence-tagged site marker

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 62 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…The BB responses of 42 Sri Lankan rice accessions/varieties (16 SLTAs and 26 SLNIVs) from the Yala season of 2017 was previously reported in Nanayakkara et al (2020). In the current study, the estimated median score (EMS) reported for these 42 Sri…”
Section: Methodology Bacterial Blight Disease Responses Of the Core R...mentioning
confidence: 59%
See 3 more Smart Citations
“…The BB responses of 42 Sri Lankan rice accessions/varieties (16 SLTAs and 26 SLNIVs) from the Yala season of 2017 was previously reported in Nanayakkara et al (2020). In the current study, the estimated median score (EMS) reported for these 42 Sri…”
Section: Methodology Bacterial Blight Disease Responses Of the Core R...mentioning
confidence: 59%
“…Molecular marker-assisted selection (MAS) can be used to introgress the resistance alleles of these Xa genes into elite rice varieties. In previous studies, intragenic markers Xa4_F/R and ABUOP0001_F/R were used to track BB resistance alleles of genes Xa4 and Xa21, respectively (Hajira et al, 2016;Yap et al, 2016;Nanayakkara et al, 2020). For the gene Xa38, the linked marker Os04g53050-1_F/R was recommended (Bhasin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The irrigation network allows dry zone farmers to cultivate rice in both wet and dry seasons either as a rainfed or an irrigated crop. However, rice cultivation in other ACZs is largely practiced as a rainfed crop with a lesser dependency on irrigation water (Amarasingha et al 2018;Nanayakkara et al 2020). Depending on the seasonal water availability, lowland rice-based cropping systems operate either as intensive rice-rice, rice-vegetable, or rice-other field crops (OFC; such as maize, mungbean, cowpea, millets, chili, soybean, or vegetables) or rice-fallow rotations (Ratnayake et al 2017).…”
Section: Introductionmentioning
confidence: 99%